Positive-charge tuned gelatin hydrogel-siSPARC injectable for siRNA anti-scarring therapy in post glaucoma filtration surgery - Chun, Yong Yao (2021)
Small interfering RNA (siRNA) therapy is a promising epigenetic silencing strategy. However, its widespread adoption has been severely impeded by its ineffective delivery into the cellular environment. Here, a biocompatible injectable gelatin-based hydrogel with positive-charge tuned surface charge is presented as an effective platform for siRNA protection and delivery. We demonstrate a two-step synthesis of a gelatin-tyramine (Gtn-Tyr) hydrogel with simultaneous charge tunability and crosslinking ability. We discuss how different physiochemical properties of the hydrogel interact with siSPARC (siRNA for secreted protein, acidic and rich in cysteine), and study the positive-charge tuned gelatin hydrogel as an effective delivery platform for siSPARC in anti-fibrotic treatment. Through in vitro studies using mouse tenon fibroblasts, the positive-charge tuned Gtn-Tyr hydrogel shows sustained siSPARC cellular internalization and effective SPARC silencing with excellent biocompatibility. Similarly, the same hydrogel platform delivering siSPARC in an in vivo assessment employing a rabbit model shows an effective reduction in subconjunctival scarring in post glaucoma filtration surgery, and is non-cytotoxic compared to a commonly used anti-scarring agent, mitomycin-C. Overall, the current siRNA delivery strategy involving the positive-charge tuned gelatin hydrogel shows effective delivery of gene silencing siSPARC for anti-fibrotic treatment. The current charge tunable hydrogel delivery system is simple to fabricate and highly scalable. We believe this delivery platform has strong translational potential for effective siRNA delivery and epigenetic silencing therapy.